Study on A Catalyst Degradation Mechanism and A Suppression Method for Sour Shift Reaction - Ryohei Inagaki; Takashi Sasaki; Hidehiro Iizuka; Tomoko Suzuki (Journal of Chemical Engineering of Japan)
As a highly efficient coal-fired power-generation technology called the integrated coal gasification combined cycle with CO2 capture and storage (IGCC-CCS) technology is being developed. With IGCC-CCS, coal gasification gas, which is mainly composed of CO, reacts with steam on a shift catalyst to produce H2 and CO2. After CO2 is separated, the H2 is used as fuel to generate power by combining a gas turbine and steam turbine. The IGCC-CCS includes a sour-shift process, which produces H2 and CO2 by catalytic reaction of CO and H2O. One of the challenges facing the practical application of this technology is the durability of the catalyst used in this shift process. This durability requires investigation from two perspectives: maintaining long-term operating performance and suppressing deterioration during startup operations, which are non-steady-state operations. This study focused on the latter. Specifically, we verified whether the catalyst degraded by trace O2 contained in the N2 used for the startup operation, analyzed the mechanism behind this, and investigated a new startup method that is based on this degradation mechanism. We first found that the catalyst degrades due to trace O2 contained in the N2 used during the temperature-increase process at startup. It was verified that the MoS2, which is the active site of the catalyst, is oxidized to MoOx by the trace O2, resulting in a decrease in the amount of sulfur in the catalyst, which in turn causes a decrease in shift activity. We also devised a startup method for suppressing catalyst degradation during startup that involves adding H2 or H2S to the gas used for startup operation and confirmed the effect of suppressing catalyst degradation. We found that catalyst degradation during startup operation can be suppressed by adding H2 at a ratio of H2/O2=4 mol/mol relative to the amount of O2 contained in the N2.